Analisis Yuridis Terhadap Penentuan Status Barang Bukti Pada Putusan Perkara Pidana Pengangkutan Mineral Tanpa Izin di Pengadilan Negeri Marisa - M. Burhanuddin Yusuf; Rustam Hs. Akili; Arifin Tumuhulawa (LPPM Universitas Bina Taruna Gorontalo, 2024)
This study aims to review and analyze the judge's considerations in determining the status of evidence in the criminal case concerning the transportation of minerals without permission, as outlined in Decision Number 4/Pid.Sus/2023/PN Mar. Additionally, it seeks to examine the correlation between these judicial considerations and the application of criminal sanctions imposed on perpetrators of the crime of unauthorized mineral transportation in the same court decision. The research employs a normative juridical method. The findings indicate that the judge's considerations in determining the status of evidence in this case are consistent with the application of Law Enforcement Theory, Justice Theory, Criminal Responsibility Theory, Legal Certainty Theory, and Criminal Theory, and are based on the theories of punishment and criminal liability. The analysis demonstrates a close correlation between the judge's considerations regarding evidence and the application of criminal sanctions on the offenders, in alignment with Court Decision Number 4/Pid.Sus/2023/PN Mar.